Study of Biomarker Discordance between Primary and Recurrent Sites and its Clinical Implications in Metastatic Breast Cancer : A Single Institutional Study from India - Shanthala, S.; Amirtham, Usha; Gopal, Champaka; N., Suma M.; Jacob, Linu; Babu, Govinda (South Asian Journal of Cancer, 2023)
Immunophenotypic discordance of receptors between primary and metastatic sites significantly impacts treatment outcomes. Current international guidelines recommend rebiopsy of accessible metastatic lesions to reassess tissue biomarkers. While existing literature on biomarker changes is conflicting and heterogeneous, similar studies on the Indian cohort of breast cancer patients are lacking. In this context, we aimed to evaluate the frequencies of biomarker changes between biopsies from primary and recurrent sites, and their association with various clinicopathological characteristics, including the type of metastasis and treatment in metastatic breast cancer (MBC) patients. This is an ambispective study performed at a single center. Immunohistochemical (IHC) expression of paired primary and recurrence samples of MBC patients was reviewed for the expression of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor 2 (HER2), and Ki-67. Concordance, loss, and gain of receptors were assessed based on the Allred scores for ER, PR, and HER2. Ki-67 was assessed based on a 14% cutoff. Further, receptor changes were studied in relation to age, menopausal status, morphology, grade, stage, metastatic sites, interval between biopsies, and treatment. At progression, biopsies were obtained from 41.18% of locoregional recurrence and 58.82% of metastatic sites. Despite high discordance of 47% for ER and 68.6% for PR, true receptor conversion was observed in 9.8%, 21.56%, and 5.88% for ER, PR, and HER2, respectively. There was a significant correlation between age and ER discordance (p = 0.029). Loss in PR significantly correlated with a gain in Ki-67. Of all the metastatic sites, the lung was significantly associated with PR and Ki-67 concordance (p = 0.008 and p = 0.0425, respectively). Discordance of receptors was neither related to the sites of biopsy (local recurrence or metastatic site) nor to the time interval between biopsies, prior chemotherapy, or hormone therapy. In conclusion, metastatic progression of the disease is accompanied by age-dependent discordance of ER. Unparalleled changes in PR in relation to ER suggest that ER-independent pathways may influence PR expression in MBC. Furthermore, the concurrence of PR loss with Ki-67 gain indicates an aggressive phenotype with disease progression. Hence, follow-up testing of samples for receptor expression is beneficial in determining prognosis and guiding therapeutic decisions.
Keywords: ER; PR; receptor; discordance; metastatic; breast; cancer